2010
DOI: 10.1292/jvms.09-0314
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Porcine Circovirus Type 2 (PCV2) Vaccination on PCV2 Genotypes at Japanese Pig Farms

Abstract: ABSTRACT. Infection of pigs with porcine circovirus type 2 (PCV2) causes a variety of disorders collectively referred to as porcine circovirus associated diseases (PCVADs). PCV2 isolates can be classified into two major types: PCV2a and PCV2b. In the present study, effects of vaccination on antibody titers in sera, PCV2 viremia, and shedding of PCV2 in feces were studied on Japanese commercial pig farms where vaccination of piglets against PCV2 was performed using commercially available vaccines. The effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…In an effort to identify the PCV2 subtypes associated with the swine CAFOs, we amplified from the sample DNAs by PCR a ∼300 bp highly variable (capsid protein) region of the PCV2 genome, cloned the products and sequenced ∼400 representative clones. Phylogenetic analysis of the sequences (Figure 4) indicates that several PCV2 relatedness groups, subspecies, occurred in the two swine facilities, including subspecies variously termed PCV2, PCV2a, PCV2b, PCV1/2a, and PCV2e (Morozov et al 1998;Olvera et al 2007;Gagnon et al 2010;Beach et al 2010;Takahagi et al 2010). No novel PCV2 clades were detected.…”
Section: Analysis Of Aerosolized Virusesmentioning
confidence: 98%
“…In an effort to identify the PCV2 subtypes associated with the swine CAFOs, we amplified from the sample DNAs by PCR a ∼300 bp highly variable (capsid protein) region of the PCV2 genome, cloned the products and sequenced ∼400 representative clones. Phylogenetic analysis of the sequences (Figure 4) indicates that several PCV2 relatedness groups, subspecies, occurred in the two swine facilities, including subspecies variously termed PCV2, PCV2a, PCV2b, PCV1/2a, and PCV2e (Morozov et al 1998;Olvera et al 2007;Gagnon et al 2010;Beach et al 2010;Takahagi et al 2010). No novel PCV2 clades were detected.…”
Section: Analysis Of Aerosolized Virusesmentioning
confidence: 98%
“…The large-scale vaccination in the pig producing industry might contribute to the PCV2 variations or mutations, which might be the important mechanism to escape immune elimination initiated by host immune response. Recent evidence from field trials in Japan indicates that efficacy of PCV2 vaccination may depend on the PCV2 genotype [29]. Moreover, Opriessnig et al has demonstrated a similar study that PCV1-2b vaccination significantly reduced the prevalence and amount of PCV2 viremia compared to the PCV1-2a vaccination [30].…”
Section: Discussionmentioning
confidence: 97%
“…In August 2013, sick animals presented wasting, anorexia, dyspnea and labored breathing starting at approximately 8 weeks of age, with an overall morbidity of 70 % and mortality of 40 %. Nineteen serum samples from randomly selected, clinically unaffected 8-week-old pigs (n = 05; samples 01-05) and clinically affected (n = 04, samples 06-09), clinically affected 10-week-old pigs (n = 05; samples [10][11][12][13][14] and sows (n = 05; samples [15][16][17][18][19] were tested for the presence of PCV2 antibodies by ELISA and for the presence of the PCV2 genome by PCR. Clinically affected 8-and 10-week-old pigs (samples 06-14) were euthanized and samples of lung, lymph node, liver, ileum, spleen and kidney were collected for histological and immunohistochemical analysis as described previously [20][21][22].…”
Section: Herd and Samplesmentioning
confidence: 99%
“…Thus, different genotypes of PCV2, called PCV2a, PCV2b and PCV2c, have been grouped according to differences in the primary structure of their Cap proteins [8]. All currently available commercial vaccines contain the PCV2a genotype and have been effective in preventing PCVAD until recently [9][10][11][12][13]. Much of this is explained by the existence of varying degrees of cross-protection between the different genotypes, a consequence of the presence of immunogenic regions that are conserved among these groups [3,14].…”
Section: Introductionmentioning
confidence: 99%